2017
DOI: 10.1039/c6ra28531g
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale structured germanium nanoripples as templates for bioactive surfaces

Abstract: A novel two-step transfer process, that produces by nanoimprinting lithography biocompatible polymeric nanowired ripples, starting from germanium surfaces nanopatterned by irradiating gold ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 41 publications
0
14
0
1
Order By: Relevance
“…After having fabricated the PFPE intermediate molds as previously described, we performed thermal NIL to transfer the nanostructures on Cyclic Olefin Copolymer (COC) foils. The process parameters were previously optimized for this copolymer as follows: T imprint = 150 °C (T COC g = 134 °C, t = 300 s, P = 50 bar, T cool-down = 80 °C) [ 18 , 19 , 20 ]. The characteristic of low surface energy of PFPE also helped in this case, thus facilitating the final detachment of the imprinted plastics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After having fabricated the PFPE intermediate molds as previously described, we performed thermal NIL to transfer the nanostructures on Cyclic Olefin Copolymer (COC) foils. The process parameters were previously optimized for this copolymer as follows: T imprint = 150 °C (T COC g = 134 °C, t = 300 s, P = 50 bar, T cool-down = 80 °C) [ 18 , 19 , 20 ]. The characteristic of low surface energy of PFPE also helped in this case, thus facilitating the final detachment of the imprinted plastics.…”
Section: Resultsmentioning
confidence: 99%
“…PFPE resin (FLUOROLINK ® MD 700, Solvay Speciality Polymers, Bollate, Italy) was mixed with 3% w / w photoinitiator Darocure 1173 (C 10 H 12 O 2 , 405655 Sigma Aldrich, Milano, Italy), poured on top of the PMMA surfaces, and crosslinked by UV-light (365 nm, 25 mW·cm −2 ). The exposure was performed in two steps, which was reported in References [ 18 , 19 ]. Briefly, the samples were kept for 180 s in nitrogen atmosphere and then were kept for 60 s in air.…”
Section: Methodsmentioning
confidence: 99%
“…For periodic nanopatterns, the x ‐projection gives the corresponding wave‐vector direction and l represents the ripple wavelength λ . To measure the average difference between peak heights and valley depths of the ripples, called mean roughness depth R z , the maximum vertical distances D l between the highest and lowest data points within one correlation length and for all the possible lengths l contained in a single x ‐line scan were calculated and summed to provide the final R z average value (more details about this calculation can be found in Dell'Anna et al ., 2017). The D l histograms were computed together with the corresponding probability distribution function (PDF), calculated with a Gaussian kernel density estimation by Scott's method (Scott, 1992).…”
Section: Methodsmentioning
confidence: 99%
“…The use of nanorippled surfaces as periodic templates for thin‐film (Fassbender et al ., 2009) and nanoparticle deposition (Ranjan & Stefan Facsko, 2012) is particularly promising to tailor specific magnetic or optical properties through the introduction of a spatial anisotropy. Recently, it has been shown that highly regular ion‐induced nanorippled surfaces can be transferred onto biocompatible polymeric substrates (Dell'Anna et al ., 2017) and used in a neural cell adhesion and spatial organization study (Masciullo et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Two strategies have been reported so far. Dell'Anna et al employed thermal nanoimprinting lithography via an intermediate mold [105]. This intermediate mold was fabricated by UV crosslinking of a perfluoropolyether (PFPE) resin on a nanorippled Ge surface with about 300 nm periodicity.…”
Section: Pattern Transfermentioning
confidence: 99%